Integrated Operational System Enterprise Architec-ture Designing Using TOGAF-ADM Method Case Study at PT. XYZ (Construction Company) - Fazlurrani Izzattisselim; Nilo Legowo (Eduvest - Journal of Universal Studies, 2024)
XYZ is a construction company that belongs to the civil sector of construction, especially in the field of water management and waterwaste management in private and public projects. In its journey, PT XYZ continues to grow following the development of existing technology. However, in its development in the implementation of information systems, it turns out that some of the main processes at PT XYZ are still carried out manually. So that problems arise and disrupt the business processes of PT. XYZ. These problems include problems with data integration, communication and loss of information due to certain things. Especially in processes that are still done manually such as warehouse and project management. From this problem, an analysis will be made that will identify the problem in detail with company XYZ. So the idea of developing an integrated operational system emerged that would be built according to the Enterprise Architecture (EA) method. EA can be analogous to when building a building, a model, design and design of the building is needed. These things are needed as models and foundations for the design. Similar to the implementation of information systems, before its development, the basis and foundation of the design are needed in the form of information system models or architectures. In this research, the EA method that will be used is TOGAF-ADM. This method was chosen because TOGAF ADM is a complex method that can meet all EA development needs, so it is used based on organizational needs.